ASSESSMENT OF THE TEACHER'S MEDIA-CULTURE AS THE COMPONENT OF QUALIFICATION PORTRAIT - T. A. Boronenko; A. V. Kaysina; V. S. Fedotova (Образование и наука)
Introduction. Nowadays, there is a growing recognition of the role of media in life and educational practice of the person, determined by the development of media education and media educational activities. This requires that modern teachers must possess a media culture, to work effectively in a new media environment, to form media competence and media literacy among students. The aims of the present publication are the following: to consider the phenomenon “media culture” as an important part of the modern teacher’s professional portrait complied according to the professional standards for teachers; to form the basis for assessment toolkit for monitoring the teacher’s culture component. Methodology and research methods. Methodological framework of the research is based on the concepts of systematic, culturological, environmental and personal-activity approaches. Basic research methods involve: a theoretical analysis of psychological and pedagogical literature, generalization of practical experience in media education; diagnostic methods (questionnaire, survey, statistical data collection and processing), pedagogical experiment. Results and scientific novelty. In the authors’ view, media culture is understood as a determinant of a qualification portrait of the teacher at the present stage of education development. The authors state the positive role of this type of the teacher’s culture in formation of his/her professional qualities, such as critical rationality, independence of thinking, ability to cope with imposing by media of the certain points of view caused by external interests. It is shown that the high level of media culture allows the teacher: to be guided in the media environment as specifically organized sign-oriented visual and emotional environment; to design the professional activity in the field of media education, creating new information and knowledge by means of available tools and formats of the media; to choose effective strategies of individual training of school students in the media environment. Pedagogical conditions of formation of media culture of the teacher and the need for their diagnostics are denoted. The authors have scientifically reasoned the criteria and indicators for assessment of levels of the teacher’ media culture which had been successfully approved during the experiment on the advanced training courses for teachers of the Leningrad region. Practical significance. The proposed criteria and indicators have considerable practical scope of application in assessment of professional characteristics of the teacher in the context of the requirements of the professional standard for teachers.